Nicotinic receptors as SARS-CoV-2 spike co-receptors?. (January 2022) - Dormoy, Valérian; Perotin, Jeanne-Marie; Gosset, Philippe; Maskos, Uwe; Polette, Myriam; Deslée, Gaëtan
Abstract: Nicotinic acetylcholine receptors (nAChRs) play an important role in homeostasis and respiratory diseases. Controversies regarding the association between COVID-19 hospitalizations and smoking suggest that nAChRs may contribute to SARS-CoV-2 respiratory syndrome. We recently detailed the expression and localization of all nAChR subunits in the human lung. Since virus association with nAChRs has been shown in the past, we hypothesize that nAChR subunits act as SARS-CoV-2 Spike co-receptors. Based on sequence alignment analysis, we report domains of high molecular similarities in nAChRs with the binding domain of hACE2 for SARS-CoV-2 Spike protein. This hypothesis supported by in silico pilot data provides a rational for the modelling and the in vitro experimental validation of the interaction between SARS-CoV-2 and the nAChRs.